Tracking millennial-scale Holocene glacial advance and retreat using osmium isotopes: Insights from the Greenland ice sheet. (15th April 2016) - Rooney, Alan D.; Selby, David; Lloyd, Jeremy M.; Roberts, David H.; Lückge, Andreas; Sageman, Bradley B.; Prouty, Nancy G.
Abstract: High-resolution Os isotope stratigraphy can aid in reconstructing Pleistocene ice sheet fluctuation and elucidating the role of local and regional weathering fluxes on the marine Os residence time. This paper presents new Os isotope data from ocean cores adjacent to the West Greenland ice sheet that have excellent chronological controls. Cores MSM-520 and DA00-06 represent distal to proximal sites adjacent to two West Greenland ice streams. Core MSM-520 has a steadily decreasing Os signal over the last 10 kyr ( 187 Os/ 188 Os = 1.35–0.81). In contrast, Os isotopes from core DA00-06 (proximal to the calving front of Jakobshavn Isbræ) highlight four stages of ice stream retreat and advance over the past 10 kyr ( 187 Os/ 188 Os = 2.31; 1.68; 2.09; 1.47). Our high-resolution chemostratigraphic records provide vital benchmarks for ice-sheet modelers as we attempt to better constrain the future response of major ice sheets to climate change. Variations in Os isotope composition from sediment and macro-algae (seaweed) sourced from regional and global settings serve to emphasize the overwhelming effect weathering sources have on seawater Os isotope composition. Further, these findings demonstrate that the residence time of Os is shorter than previous estimates of ∼10 4  yr. Highlights: Here we present new Holocene Os isotope data from distal and proximal sediment cores from West Greenland. These data can be correlated to ice stream activity and document ice stream retreat and advance over the past 10 kyr. The global sample suite highlights considerable variations in seawater Os isotope composition in well-mixed ocean basins. The data presented here confirms that the marine residence time of Os is shorter than previously thought.